Adhesion of Leukocytes to Growing Arterial Thrombi - Hagberg, Inger Anne; Roald, Helge Einar; Lyberg, Torstein (Thrombosis and Haemostasis, 1998)
Since the role of leukocytes found present in thrombi and haemo-static plugs is not clearly understood, we have investigated the interaction between leukocytes and growing thrombi in a human ex vivo model of arterial thrombogenesis. At a wall shear rate characteristic of moderately stenosed arteries (2600 s–1), granulocytes selectively accumulated at the luminal surface of platelet thrombi. The leukocyte adhesion seemed independent of fibrin formation and was clearly correlated to thrombus growth and platelet activation. In contrast, flow cytometry revealed that the expression of adhesion molecules (CD11a, CD11b, CD11c, CD3, CD14, CD62L, HLA-DR and binding of fibrinogen) on the surface of circulating leukocytes passing the thrombi was, on short term conditions (15 min), independent of thrombus growth. The adhered granulocytes probably play a pivotal role in limiting the size of the evolving thrombi, as suggested by our electron micrographs of the arterial thrombi showing lysed and phagocytosed platelets. Thus, granulocytes might play an active role in the acute/semiacute phase of local thromboregulation.